2009
DOI: 10.1038/npp.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Glutamate/Glutamine Levels May Mediate Cytidine’s Efficacy in Treating Bipolar Depression: A Longitudinal Proton Magnetic Resonance Spectroscopy Study

Abstract: Targeting the glutamatergic system has been suggested as a promising new option for developing treatment strategies for bipolar depression. Cytidine, a pyrimidine, may exert therapeutic effects through a pathway that leads to altered neuronal-glial glutamate cycling. Pyrimidines are also known to exert beneficial effects on cerebral phospholipid metabolism, catecholamine synthesis, and mitochondrial function, which have each been linked to the pathophysiology of bipolar depression. This study was aimed at dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 69 publications
(97 reference statements)
1
35
0
Order By: Relevance
“…The midfrontal VOI was positioned by using a priori rules, as in earlier publications (Ham et al , 2007; Sung et al , 2007; Yoon et al , 2009) (Figure 1). Throughout the entire study period, the same examiner positioned study subjects in the basis set and reported as mmol/l (Provencher, 2001; Barker et al , 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The midfrontal VOI was positioned by using a priori rules, as in earlier publications (Ham et al , 2007; Sung et al , 2007; Yoon et al , 2009) (Figure 1). Throughout the entire study period, the same examiner positioned study subjects in the basis set and reported as mmol/l (Provencher, 2001; Barker et al , 1993).…”
Section: Methodsmentioning
confidence: 99%
“…However, this theory alone cannot fully explain the neurobiology of depression; therefore, other neurotransmission systems and signaling pathways have been implicated in the pathophysiological mechanisms of depression, such as acetylcholine (ACh), glutamate, gamma-aminobutyric acid (GABA), and endogenous opiates. [28][29][30][31][32] Functional imaging studies have shown that blood flow and glucose levels are higher in some parts of the brain (e.g., the frontal cortex, amygdala, thalamus, and lower parts of the striatum) of patients with major depression as compared with controls.…”
Section: Animal Models Of Depressionmentioning
confidence: 99%
“…Studies of pyrimidines in adults with bipolar disorder have been promising as monotherapy (Repligen 2006(Repligen , 2008Jensen et al 2008) and as an adjunct to valproate (Yoon et al 2009). Notably, participants treated with cytidine þ valproate in the latter study experienced a rapid improvement in depressive symptoms in weeks 1-4, when compared with placebo þ valproate patients.…”
Section: Uridine Bipolar Case Seriesmentioning
confidence: 99%
“…Pyrimidines have beneficial effects on cerebral phospholipid metabolism (Cansev 2006), catecholamine synthesis (Martinet et al 1978(Martinet et al , 1979, and mitochondrial function (Lehninger et al 2008)-each of which has been linked to the pathophysiology of bipolar disorder (Yoon et al 2009). The pyrimidines that have been studied as treatments for adults with bipolar depression include cytidine (Yoon et al 2009) and triacetyluridine ( Jensen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation